2014
DOI: 10.1016/j.jenvrad.2013.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Radiocesium contamination of the web spider Nephila clavata (Nephilidae: Arachnida) 1.5 years after the Fukushima Dai-ichi Nuclear Power Plant accident

Abstract: We measured the concentrations of radiocesium ((134)Cs and (137)Cs) in a large web spider, Nephila clavata L. Koch (Nephilidae: Arachnida), collected at three sites at different distances from the Fukushima Dai-ichi Nuclear Power Plant about 1.5 y after the accident in March 2011. The radiocesium concentrations in spiders were highest in a streamside secondary forest 33 km northwest of the power plant: mean ± a standard deviation of 2.401 ± 1.197 Bq g(-1) dry for (134)Cs and 3.955 ± 1.756 Bq g(-1) dry for (137… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 15 publications
2
16
1
Order By: Relevance
“…While Ayabe et al (2014) reported a significant relationship between body size and contamination level in the spider N. clavata, we observed a positive, but not significant, relationship between accumulated radiocesium and body size in R. tagoi tagoi. This probably was related to the fact that contamination levels in frogs collected at sites with higher air radiation dose rates were approximately 10-fold higher than those at the lower sites.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…While Ayabe et al (2014) reported a significant relationship between body size and contamination level in the spider N. clavata, we observed a positive, but not significant, relationship between accumulated radiocesium and body size in R. tagoi tagoi. This probably was related to the fact that contamination levels in frogs collected at sites with higher air radiation dose rates were approximately 10-fold higher than those at the lower sites.…”
Section: Discussioncontrasting
confidence: 93%
“…During the field survey, we attached a personal dosimeter (PM1610, Polimaster Ltd., Belarus) 1 m above the ground and recorded air radiation dose rates of gamma radiation (mSv$h À1 ) at each sampling site, consistent with other studies (e.g., Hasegawa et al, 2013;Ayabe et al, 2014;Yoshimura and Akama, 2014). These dose rates were presented as average values of measurements made at 3e5 locations in which frogs were caught in each sampling site.…”
Section: Field Surveymentioning
confidence: 87%
See 1 more Smart Citation
“…Ayabe et al (2014) reported that a relatively high concentration of radiocesium was detected in some large spiders. This fact indicated that radiocesium was transferred to the web spider, which is a secondary consumer in the food web.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that there was a decrease in the survival rate and high malformation rate in aphids (Akimoto, 2014) and pale grass blue butterfly (Hiyama et al, 2012) in radiocesium-contaminated areas due to the FDNPP accident. The web spider in the class of arachnida (Ayabe et al, 2014) and aquatic insects (Yoshimura and Akama, 2014) also incorporated radiocesium. However, little is known about the transfer of radiocesium from food (primary producers) to insects (consumer) in the food web.…”
Section: Introductionmentioning
confidence: 99%